2019
DOI: 10.1111/1747-0080.12514
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between pre‐pregnancy dietary patterns adherence and risk of gestational diabetes mellitus in Iran: A case–control study

Abstract: Aim The present study aimed to investigate major dietary patterns and their association with risk of gestational diabetes mellitus (GDM) in Yazd city located in Iran. Methods This case–control designed study was conducted at six healthcare centres. Two hundred and seventy‐eight pregnant women who referred for GDM screening participated. Dietary assessment was carried out by using a 67‐item validated food frequency questionnaire to evaluate dietary history of participants during the last year. Principal compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 39 publications
(99 reference statements)
1
35
0
1
Order By: Relevance
“…Asadi et al 16 studied the dietary habits of pregnant woman, with and without GDM, in a randomly selected population. Based on their systematic observations, they identified two patterns of dietary habits, which were documented as “prudent dietary pattern” and “Western dietary pattern.” The statistical analysis they performed documented that the probability of GDM occurrence under the prudent dietary pattern was lower.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Asadi et al 16 studied the dietary habits of pregnant woman, with and without GDM, in a randomly selected population. Based on their systematic observations, they identified two patterns of dietary habits, which were documented as “prudent dietary pattern” and “Western dietary pattern.” The statistical analysis they performed documented that the probability of GDM occurrence under the prudent dietary pattern was lower.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies 16,17,19 found a protective association against GDM of a Mediterranean or prudent diet prior to and during pregnancy in contrast to a Western diet. Asadi et al recorded the diet habits prior to pregnancy and Assaf-Balut et al during early pregnancy, both seeing lower rates of GDM in prudent and Mediterranean diets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been replicated by the ESTEEM multicentre randomised trial in the UK ( 86 ) . Similarly, Asadi et al showed in a case–control study at six healthcare centres in Iran that pre-pregnancy adherence to the prudent dietary pattern was significantly associated with reduced risk of GDM ( 87 ) . The prudent dietary pattern was associated with ‘high intakes of fruits, low-fat dairy, potato, egg, fish, poultry, nuts, organs meat and red meat’.…”
Section: Glycaemic Control Beyond Energies: a Lesson From Pistachiosmentioning
confidence: 94%
“…Given that Western‐style diets are typically low in plant‐based foods, the study reported in this issue by Zamani et al investigated the link between a plant‐based diet and gestational diabetes mellitus (GDM) in Iranian women, finding a 53% reduced risk of developing GDM among those consuming a diet high in plant‐based foods. In contrast, Asadi et al study examined the association between pre‐pregnancy dietary patterns and the risk of GDM in Iranian women. This study found that a prudent dietary pattern characterised by a high consumption of fruits, low‐fat dairy, potato, egg, fish, poultry, nuts, organ meat and red meat, was associated with a reduced risk of GDM, but no significant relationship was found between Western‐style dietary patterns and GDM risk.…”
Section: Diet Patterns and Health Outcomesmentioning
confidence: 97%